2016
DOI: 10.1016/j.cmi.2015.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of renal safety and efficacy of telbivudine, entecavir and tenofovir treatment in chronic hepatitis B patients: real world experience

Abstract: This study aims to assess the nephrotoxicity and efficacy of tenofovir disoproxil fumarate (tenofovir), telbivudine and entecavir. A retrospective study of 587 patients with chronic hepatitis B treated with tenofovir (n = 170), telbivudine (n = 184) and entecavir (n = 233) for at least 1 year. Renal function and efficacy were assessed. The estimated glomerular filtration rate (eGFR) decreased significantly in the tenofovir group after a mean of 17 months treatment (from 92.2 to 85.6 mL/min/1.73 m(2), p < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
2
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 25 publications
3
55
2
8
Order By: Relevance
“…Our results show that the rate of the long-term telbivudine treatment-induced HBeAg seroconversion is relatively higher than the other four NAs. However, the drug resistance rate of telbivudine increases with prolonged treatment time, thereby limiting its application [53]. Kranidioti et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the rate of the long-term telbivudine treatment-induced HBeAg seroconversion is relatively higher than the other four NAs. However, the drug resistance rate of telbivudine increases with prolonged treatment time, thereby limiting its application [53]. Kranidioti et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, the LdT+ADV group had a higher mean eGFR during 144 weeks of treatment ( P <0.05), which is compatible with a previous monotherapy study [14], which also showed that ADV monotherapy may impair renal function. Furthermore, although TDF had better antiviral potency than LdT and is the newest medication for hepatitis B recommended by the American Association for the Study of Liver Diseases (AASLD), LdT was found to have a more superior renal protection than TDF [48, 49]. The mechanism of improvement in renal function after combined therapy remains to be determined but may be related with HBV eradication.…”
Section: Discussionmentioning
confidence: 99%
“…Sebbene negli studi clinici randomizzati, controllati, in pazienti selezionati con epatite cronica B, il trattamento con TDF si sia dimostrato ben tollerato e senza segnalazioni di tossicità renale clinicamente significativa, l'esperienza clinica real life ha riportato casi di compromissione della funzione renale fino all'insufficienza renale e alla sindrome di Fanconi [6,7,[10][11][12][13][14][15][16][17][18][19][32][33][34][35][36][37][38][39]. Spesso i fattori di rischio per un peggioramento della funzione renale sono l'età avanzata, l'ipertensione arteriosa e una preesistente riduzione del filtrato glomerulare.…”
Section: Discussioneunclassified
“…Tra i NUC approvati, entecavir (ETV) e tenofovir disoproxil fumarato (TDF) sono raccomandati in prima linea nel trattamento dell'epatite cronica B, poiché entrambi sono antivirali potenti e con elevata barriera alla resistenza [1][2][3]. Negli studi registrativi e negli studi clinici a lungo termine, sia ETV che TDF hanno mostrato un profilo di sicurezza favorevole [4][5][6][7][8][9][10][11], anche se recentemente sono stati segnalati nella pratica clinica eventi avversi a livello Efficacia e sicurezza di entecavir dopo switch da tenofovir per comparsa di effetti collaterali renali M. Viganò renale e osseo nei pazienti trattati per lungo tempo con TDF [6,7,[10][11][12][13][14][15][16][17][18][19]. I meccanismi alla base della potenziale tossicità dei NUC sono legati alla loro capacità di inibire la DNA polimerasi ϒ mitocondriale umana quando le concentrazioni intracellulari dei NUC superano una soglia critica [12].…”
Section: Introduzioneunclassified